Correlation Between Maxillary Morphology and Sinus Dimensions in Skeletal Class I, II, and III Subjects: A Comparative Study - Shaikh, Nida; Shastri, Dipti; Tandon, Pradeep; Singh, Gyan Prakash (Journal of Dentistry Indonesia, 2026)
Background: This study aimed to evaluate variations in maxillary and sinus morphology and their correlations with skeletal malocclusion patterns using CBCT. Methods: This retrospective study analyzed CBCT records of 70 subjects aged 17–40 years, divided into three groups: Skeletal Class I (N = 25), Class II (N = 25), and Class III (N = 20). Five maxillary skeletal and four sinus parameters were assessed. Intergroup comparisons were performed using one-way analysis of variance (ANOVA) followed by Tukey’s post hoc test. Correlations were evaluated using Pearson’s correlation test. Intra-observer reliability was assessed by re-measuring 8 randomly selected CBCT scans after a two-week interval, and intraclass correlation coefficients (ICCs) were calculated to confirm measurement consistency. Results: Significant intergroup differences were found in ANS-PNS, Cd-A, and Zm-Zm, with skeletal Class III subjects showing consistently reduced values. Maxillary sinus dimensions did not differ significantly among groups. Skeletal Class III subjects demonstrated stronger correlations between sinus and skeletal parameters compared to Class I and II. Conclusions: Although maxillary sinus dimensions did not differ significantly among skeletal classes, notable correlations with maxillary skeletal morphology, especially in Class III malocclusion, were observed. These findings may have relevance for diagnostic assessment and treatment planning in orthodontic and surgical cases.